Psychometric properties of the wong and law emotional intelligence scale in a colombian manager sample (2022)
Within the organizational field, emotional intelligence is linked to socially competent behaviors, which allow the development of labor and organizational abilities necessary for professional development. Thus, in workers, emotional intelligence is related to a wide range of organizational variables. The purpose of the present study was to evaluate the psychometric properties of the Wong and Law Emotional Intelligence Scale (WLEIS) in the Colombian context, specifically, in a population of managers. The study was instrumental. The sample consists of 489 Colombian managers, obtained through non-probability sampling (a purposive sample), who work in companies located in Bogota. The results indicated that the four-factor oblique model presents favorable fit indices, as well as the higher-order model, the latter having additional theoretical support. These results indicate that it is possible to consider partial scores for each of the four factors of the WLEIS, as well as an overall emotional-intelligence score. Also, the WLEIS scores have validity evidence based on relations to other variables (convergent and discriminant evidence) and are reliable. These first findings for Colombian managers contribute to the accumulation of international evidence of emotional intelligence measured with the WLEIS.